2019
DOI: 10.1073/pnas.1901080116
|View full text |Cite
|
Sign up to set email alerts
|

On the occurrence of cytochrome P450 in viruses

Abstract: Genes encoding cytochrome P450 (CYP; P450) enzymes occur widely in the Archaea, Bacteria, and Eukarya, where they play important roles in metabolism of endogenous regulatory molecules and exogenous chemicals. We now report that genes for multiple and unique P450s occur commonly in giant viruses in the Mimiviridae, Pandoraviridae, and other families in the proposed order Megavirales. P450 genes were also identified in a herpesvirus (Ranid herpesvirus 3) and a phage (Mycobacterium phage Adler). The Adler phage P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 59 publications
0
36
0
Order By: Relevance
“…genes, encoding enzymes that are known to be essential in the metabolism of endogenous regulatory molecules and exogenous drugs, but not their ancillary enzymatic redox partners, which could be recruited from host (12). Recently, a deep analysis of 501 environmental metagenome-assembled genomes of NCLDV revealed a diversity of metabolic genes involved in nutrient uptake, light harvesting, nitrogen metabolism, glycolysis and the TCA cycle (41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…genes, encoding enzymes that are known to be essential in the metabolism of endogenous regulatory molecules and exogenous drugs, but not their ancillary enzymatic redox partners, which could be recruited from host (12). Recently, a deep analysis of 501 environmental metagenome-assembled genomes of NCLDV revealed a diversity of metabolic genes involved in nutrient uptake, light harvesting, nitrogen metabolism, glycolysis and the TCA cycle (41).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, an almost complete protein translation apparatus was discovered in Tupanvirus and Klosneuviruses (9,10). More recently, it was found that genes encoding multiple and unique cytochromes P450 monooxygenases commonly occur in giant viruses in the Mimiviridae, Pandoraviridae, and other families in the proposed order Megavirales (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Sequences of several giant viruses were found in human microbiome, but nothing is known about their interaction profile and ecological roles [94, 95]. Furthermore, it has been found that these viruses can encode genes that act on complex biochemical pathways [9698]. The wide distribution and diversity of giant viruses associated with their powerful gene arsenal, both known and unknown, can reflect the wide range of interaction strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the presence of this prosthetic group, these enzymes absorb wavelengths at 450 nm; thus, the name P450s has been assigned to these proteins [ 3 , 4 , 5 , 6 ]. Since their identification, a large number of P450s have been identified in almost all living organisms [ 7 ] and, surprisingly, in non-living entities as well [ 8 ]. The regio- and stereo-specific catalytic nature of these enzymes makes them essential for the survival of some organisms, and these enzymes are thus good drug targets in the case of pathogenic organisms [ 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%